Guru dan Peserta Didik: Strategi dalam Pembelajaran untuk Mewujudkan Merdeka Belajar di Sekolah - Haposan Simanjuntak; Rongga Uli Sipahutar; Renny Victoria Sinaga; Anita Berutu; Dwianjani E Nainggolan; Nelva Sitorus (Journal on Education, 2024)
Learning in independent learning emphasizes students being more active in being independent in carrying out their learning activities. However, in reality, students are still found who have difficulty understanding the learning and practical activities. Thus, the aim of this article is to explore a teacher's strategy in realizing freedom of learning for students through the learning process. so that the essence of independent learning can be carried out well. The method used in this research is a descriptive qualitative research method with an approach to library data sourced from journals, books and websites, where researchers study and take theories or opinions that are relevant to the study to produce conclusions. The result of this paper is that students are able to think systematically in their own way in understanding the learning delivered by educators and completing assignments and practices according to individual creativity. This is accomplished through the strategies implemented by teachers in the teaching and learning process. Thus, it is very important for an educator to have a strategy in realizing independent learning for students.